Warsztat malarski Pietera Meulenera na przykładzie obrazu Potyczka jeźdźców w krajobrazie (1647 r.) z Muzeum Narodowego w Poznaniu oraz innych dzieł malarza znajdujących się w zbiorach polskich - Kapka, Magdalena; Basiul, Elżbieta (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2013)
This paper presents technique and technology of the seventeenth-century Flemish painter Pieter Meulener, most renowned for battle scenes and landscapes with scenes. It presents an analysis of the technical structure: Encounter of Horsemen in a landscape from the collection of the National Museum in Poznan, Skirmish from the National Museum in Warsaw and Landscape with a battle scene from the National Museum in Gdansk. The presented results were supplemented with information on the seventeenth century Flemish painters’ workshop. Analysis on the technical structure of Pieter Meulener’s paintings helped to understand the rules in seventeenth century Flemish painting. In result of this research it was established that Pieter Meulener referred in his painting to the workshop of the best painters of his time. The impact of emerging new trends in painting, such as alla prima technique and the strong impact of Rubens innovation and his rich painting expression, and thus – drifting away from the established painting routines – have set a very interesting stage in the evolution of Flemish paintings techniques and technologies, which due to some open issues can be an inspiration for further research.